Pembelajaran Pendidikan Agama Islam dalam Kurikulum Merdeka di SMA Negeri 1 Tilatang Kamang - Muhammad Ali Hanafi; Charles Charles; Iswantir Iswantir; Arifmiboy Arifmiboy (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Merdeka Curriculum is a new curriculum with a foundation as a complement to the 2013 Curriculum, but in implementing the Independent Curriculum it is necessary to implement it first for teachers before teaching it to students. So that it is able to build quality student character both in the academic field and in other fields. Research is to find out PAI learning in the Merdeka Curriculum in Islamic Religious Education subjects at SMA Negeri 1 Tilatang Kamang. Data collection techniques are carried out through observation, interviews and documentation. The results of this research show that the implementation of Islamic Religious Education learning consists of 3 activities, there are preliminary activities, then core activities and closed with closing activities, plus the P5 project. Then there are problems that occur in the implementation of Islamic Religious Education learning, namely educators do not take part in training, differentiated learning is less than optimal and the mindset. So the efforts made to overcome these problems are by taking part in internal/external workshops, increasing creativity as a teacher and sharing with fellow educators or with people who know more (often ask questions).